Expression and clinical significance of AUF1 and HIF-1α in papillary thyroid carcinoma - Hao Zhang; Xiao Li; Yilin Li; Siyu Li; Gaowei Yan; Weiqin Chang (World Journal of Surgical Oncology)
Abstract Background This research investigated the correlations between the levels of AU-rich elements binding factor 1 (AUF1) and hypoxia inducible factor-1α (HIF-1α) in papillary thyroid carcinoma (PTC) with clinicopathologic characteristics. Methods A total of 117 specimens of intraoperative thyroid surgery were collected, encompassing a combination of 71 PTC tissues (papillary thyroid carcinoma), 26 nodular goiter tissues(NG), and 20 normal thyroid tissues(NT). HIF-α and AUF1 levels in PTC, nodular goiter (NG), and normal thyroid tissues were examined by immunohistochemical staining and explored the link between expression levels and clinicopathological features. Results HIF-1α and AUF1 positive expression rates were significantly greater in tissues from PTC than in NG and normal thyroid tissues, according to immunohistochemistry (IHC) studies. Furthermore, the number of cancer lesions and the metastasis of central cervical lymph nodes were connected with the positive rate of HIF-1α. Tumor size and central cervical lymph node metastases were significantly positively correlated with the AUF1 positive rate. Finally, a noteworthy positive association between HIF-1α and AUF1 expression levels was noted. Conclusions AUF1 and HIF-1α may work in concert to accelerate the development of PTC. And they may be useful biomarkers for PTC and lymph node metastases.